O ensino da história indígena na Escola Indígena São Francisco – Ti Maró (2014-2017) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The struggle for an indigenous school education is a matter debated at the present time, mainly by the Borari and Arapiuns indigenous peoples, who seek to rescue through education the culture, history, customs and appreciation of the mother tongue of this population. The present study aims to investigate the teaching of indigenous history in the São Francisco School, in the Maró TI, located in the west of Para, as well as to understand the indigenous school education, besides identifying the strategies employed by the teachers to approach the indigenous history and culture of Indian people. The methodological proposal was based on the field research, bibliographical, documentary and oral history method through interviews with teachers and caciques of TI Maró. It is known that the Borari and Arapiuns inhabit this IT and form the population of the Maró Waterfalls, Novo Lugar and São José III Villages, these peoples struggle for a differentiated education, that is directed towards their reality, fight for the process of decolonization of the curricula and the approval of a curriculum that will recognize, respect and value the culture of each people, a curriculum in which to work the content focused on the reality of the Borari and Arapium peoples. Thus, while such curricular advances do not occur, the teachers of the São Francisco School assert that they tend to work the history and indigenous culture of indigenous peoples through the use of differentiated methodologies, adjusting the content pointed out by the Education Secretary with the reality of its ethnicity, using traditional knowledge, well-known knowledge and bilingual education in Portuguese and nheengatu.
Keywords: Escola São Francisco; Ti Maró; História indígena; Educação escolar indígena; Saberes tradicionais; CNPQ:: CIÊNCIAS HUMANAS